The Role of Justice Law Enforcement By Judges In Handling Criminal Cases - Sari, Nani Widya; Yanto, Oksidelfa; Widodo, Guntarto; Rejeki , Henlia Peristiwi; Ramadan, Tubagus Ahmad (Indonesian Scientific Publication, 2025)
Law enforcement is a process of making efforts to reinforce the existing legal norms. One of the parties that plays a role in law enforcement is the judge. The role of judges in law enforcement, especially criminal law, is very urgent in the criminal justice system in Indonesia. This is because the judge is the one who decides a case through his decision which will always be the concern of justice seekers. Therefore, in handling cases, the judge is impartial and may not be influenced by any party, so that his decision can realize a sense of justice in society. The research method used in this writing is the normative legal research method using secondary data obtained through literature studies. The focus of this research is the role of judges in law enforcement, especially in handling criminal cases through their just decisions.